Understanding Societal Leadership: Strategy and Impact - Institute for Societal Leadership, (Institutional Knowledge at Singapore Management University, 2015)
This study focuses on the construct and discusses the characteristics and factors affecting the phenomenon of societal leadership. Reference is made to many worthy examples of social catalysts, innovators and leaders that the Institute for Societal Leadership (ISL) has encountered in each of the Southeast Asian countries and efforts are made to delineate the strategies that are used by societal leaders to create social impact. The study also discusses the various forms of societal leadership and ways in which effective societal leaders or social impact organisations collaborate across sectors to achieve their goals.